Exploring the impact of shock advertising on brand loyalty. - Segoe, Phemelo (The IIE, 2022)
In today’s attention economy, marketers are finding themselves hard pressed to ‘cut through the clutter’ to capture and retain audience attention. As a result, marketers are turning to shock advertising to grab attention however the impact of shock advertising remains in question. This study sought to explore the impact shock advertising has on the attitudinal and behavioural brand loyalty of young black consumers. A qualitative methodology was adopted and included the use of structured, open-ended individual interviews used to explore the attitudes and behavioural intentions of participants after being exposed to shocking adverts. Three different types of shock were analysed namely gruesome images, sexual references, and racist content as well as the inclusion of an example of positive shock. The overall findings of this study indicated that shock advertising is successful in grabbing attention; however, when it is not used for good or positive purposes, it has an overall negative impact on attitudinal or behavioural brand loyalty. This study adds to the South African literature by providing marketers and advertisers with insight into the possible responses to and ramifications of shock advertising, allowing them to make informed decisions about whether to use shock advertising instead of other methods of advertising.
Keywords: Consumer behavior; Marketing; Ethics; Shock; Brand resonance